Combatting Cocoa Swollen Shoot Virus Disease: What do we know?. (August 2017) - Andres, Christian; Gattinger, Andreas; Dzahini-Obiatey, Henry K.; Blaser, Wilma J.; Offei, Samuel K.; Six, Johan
Abstract: Cocoa Swollen Shoot Virus Disease (CSSVD) is one of the major factors limiting cocoa ( Theobroma cacao L.) productivity in West Africa. The only cure for CSSVD is to cut out visibly infected trees and the official eradication campaign in Ghana has cut out more than 200 million trees since 1946. 80 years of research on preventive control measures have mainly focused on resistance breeding, mild strain cross-protection (inoculation of cocoa seedlings with a mild strain of the virus to protect against the severe strain) and control of mealybug vectors. Meanwhile, diversification measures such as agroforestry (for shading) or barrier (strip) cropping have received less attention. Despite promising results, CSSVD is more prevalent in the field than ever before. The large body of knowledge on preventive control measures for CSSVD is fragmented and many publications are not easily accessible. Furthermore, the literature has never been systematically evaluated and quantitatively assessed. Hence, we consolidated this knowledge with an extensive literature review followed by meta-analysis to identify the pertinent research gaps. Out of 423 publications on CSSVD-related issues, we selected 34 studies, which contained 52 datasets on seven different preventive control measures. Results showed that resistance breeding and mild strain cross-protection may reduce CSSVD infection by 30 percent, while the potential of diversification measures (shading/agroforestry and barrier (strip) cropping) seems to be considerably higher (40 and 85 percent, respectively). However, there is a lack of evidence because of a low number of studies about diversification measures, indicating that our results have to be interpreted with care and calling for more research in this area. Future testing is needed to evaluate the efficacy of barrier (strip) cropping to reduce CSSVD, and address the effect of shade on CSSVD symptom severity. Furthermore, the practical relevance of different preventive control measures for farmers needs to be assessed, and shade should be considered in current breeding programs for CSSVD resistance. Graphical abstract: Fig. 1 (left) . Localisation of the eligible studies used for meta-analysis.Fig. 2 (right) . Mean difference in reduction of infection with CSSVD of different improved practices vs. control (see section 2.1). Horizontal bars show 95% confidence intervals. The numbers displayed before and in brackets (after the name of the improved practices) represent the number of comparative data pairs and number of sub-studies, respectively. Highlights: First meta-analysis about preventive control measures for CSSVD. Only a fraction of the studies on CSSVD evaluated efficacy of preventive measures. All preventive measures effectively reduced CSSVD, except for antiviral substance. Breeding, shading and barrier (strip) cropping reduced CSSVD by 30, 40 and 85%. Future research and breeding should consider barrier (strip) cropping and shade.